The causal association between maternal smoking around birth on childhood asthma: A Mendelian randomization study - Ding, Zijun; Pang, Lei; Chai, Hongqiang; Li, Fei; Wu, Ming (Frontiers in Public Health, 2022)
To explore the causal relationship between maternal smoking around birth and childhood asthma using Mendelian randomization (MR). Using the data from large-scale genome-wide association studies, we selected independent genetic loci closely related to maternal smoking around birthand maternal diseases as instrumental variables and used MR methods.In this study, we considered the inverse variance weighted method (MR-IVW), weighted median method, and MR-Egger regression.Weinvestigated the causal relationship between maternal smoking around birth and maternal diseases in childhood asthma using the odds ratio (OR) as an evaluation index. Multivariable MR (MVMR) included maternal history of Alzheimer's disease、illnesses of the mother: high blood pressure and illnesses of the mother: heart diseaseas covariates to address potential confounding. Sensitivity analyses were evaluated for weak instrument bias and pleiotropic effects. It was shown with theMR-IVW results that maternal smoking around birth increased the risk of childhood asthma by 1.5% (or = 1.0150, 95% CI: 1.0018–1.0283). After the multivariable MR method was used to correct for relevant covariates, the association effect between maternal smoking around birth and childhood asthma was still statistically significant (P < 0.05).Maternal smoking around birth increases the risk of childhood asthma.